MDEA decarburization system analysis method based on gray correlation analysis method - HE YOUBIN; YANG YE; YANG YUAN (2017)
The invention discloses an MDEA decarburization system analysis method based on a gray correlation analysis method. The MDEA decarburization system analysis method is related to an MDEA decarburization system absorption part and an MDEA decarburization system regeneration part. The reference sequence of the MDEA decarburization system absorption part is a processed natural gas CO2 content reference sequence, and the comparison sequences of the MDEA decarburization system absorption part are an air input comparison sequence, an absorber pressure comparison sequence, an intake temperature comparison sequence, an MDEA barren solution circulation volume comparison sequence, an MDEA barren solution absorber inlet temperature comparison sequence, an MDEA barren solution concentration comparison sequence, an absorber liquid level comparison sequence, an absorber top temperature comparison sequence, and an absorber bottom temperature comparison sequence. The reference sequence of the MDEA decarburization system regen